2019
DOI: 10.1063/1.5100180
|View full text |Cite
|
Sign up to set email alerts
|

The development and performance of a perforated plate burner to produce vitiated flow with negligible swirl under engine-relevant gas turbine conditions

Abstract: The development and performance of a perforated plate burner (PPB) operating using premixed natural gas and air at engine-relevant inlet temperatures and combustor pressures with thermal powers up to 1 MW is discussed. A significant benefit of using burners with simplified flow fields, such as the PPB, for experimental studies in the laboratory is the potential for decoupling the complex fluid dynamics in typical combustors from the chemical kinetics. The primary motivation for developing this burner was to us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…The headend assembly primarily consists of a perforated plate burner (PPB) operated with premixed natural gas and air and with a hydrogen pilot flame. Details of the PPB have been covered previously [45]. The PPB was used to create a hot vitiated flow with negligible swirl, which was then accelerated by the contraction section (1:41 exit-toinlet area ratio) as the flow geometry was transitioned from circular to rectangular.…”
Section: Facility Descriptionmentioning
confidence: 99%
See 3 more Smart Citations
“…The headend assembly primarily consists of a perforated plate burner (PPB) operated with premixed natural gas and air and with a hydrogen pilot flame. Details of the PPB have been covered previously [45]. The PPB was used to create a hot vitiated flow with negligible swirl, which was then accelerated by the contraction section (1:41 exit-toinlet area ratio) as the flow geometry was transitioned from circular to rectangular.…”
Section: Facility Descriptionmentioning
confidence: 99%
“…The current rig iteration features a flow transition piece, described further in the next section, between the exit of the flow contraction section and the optically accessible SCZ. The same NO X quench and sample stage that was previously used is located directly after the axial combustor to enable accurate control of the residence time by freezing the thermal NO X production in the flow [44,45]. This was achieved by radially injecting water into the combustion gas flow to reduce the gas temperature below 1300 K and a length of pipe was used to promote mixing before exhaust gases were sampled using a water-cooled probe.…”
Section: Facility Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kalt et al [9] were able to vary the turbulence intensity with only varying the position of a perforated grid placed upstream of the burner exit. Some recent works in the same research field have also been reported [10,11]. However, this type of grid poses a serious problem when high turbulence intensity combined with good homogeneity and isotropy is needed.…”
Section: Introductionmentioning
confidence: 96%